Study of Sensitivity and Noise on Magnetic FinFET (MAG-FinFET) - Khine Thandar Nyunt Swe; Amporn Poyai; Toempong Phetchakul (My University, 2023)
Three dimensional FinFET device structure is proposed as magnetic device to detect the vertical magnetic field. The region of drain contact is split into two drain contacts and the MAG-FinFET has source contact, gate contact and two drain contacts. Lorentz's force appears as Hall effect when the magnetic field is exposed to the device perpendicularly. The imbalanced drain currents at the drain contact D1 and D2 caused by the expose of magnetic field are measured, and the Hall current is obtained as the output of MAG-FinFET. The relative sensitivities of MAG-FinFET with three channel lengths are calculated. Mixed mode AC analysis simulations are done by using Sentaurus TCAD to study the impact of noise on MAG-FinFET. The fluctuations at the output nodes of Mag-FinFET can be seen as noise voltage spectral density and noise current spectral density. The short channel length of 10 nm MAG-FinFET gives the highest differential drain current and shows the best sensitivity. The limitation of minimum magnetic field is determined from the noise current spectral density obtained at bandwidth 1 Hz to 1 kHz. For channel length 10 nm MAG-FinFET, the minimum magnetic field $\mathrm{B}_{\min}\ 76\ \text{mT}/\sqrt{Hz}$ is obtained for narrow bandwidth at frequency 1 kHz. The equivalnet magnetic field Beq obtained for large frequency range is $1.28\ \mathrm{T}/\sqrt{Hz}$.
Keywords: Magnetic Field Sensors Techniques; Non-Destructive Testing Techniques; Plasma Diagnostics and Applications